Overcoming seed dormancy in Glaucium Spp. (Papaveraceae) - Elsner, Karen C., author; Hughes, Harrison G., advisor; Kelaidis, Panayoti, committee member; Fenwick, Jack, committee member (Colorado State University. Libraries, 2007)
The Horned Poppy, Glaucium sp., is a potential candidate for introduction as an herbaceous perennial to Colorado. However, its introduction has been hindered by poor germination, less than 10% in informal studies across the state. Nine seed lots of Glaucium sp., representing four different species and a hybrid harvested from four different year, were collected at Denver Botanic Gardens and used in research to develop a protocol for seed treatment to improve germination. Four different trials were conducted to evaluate germination. The first trial evaluated stratification temperatures and germination with and without light on two collection years of G. flavum. The greatest germination was 69.5% for the seeds collected in 2005 that were stratified for 45 days at 7°C and germinated with light. The seeds harvested in 2003 had 53 % germination with 7°C stratification for 45 days and germinated without light. The second trial evaluated scarification treatments, hot water, concentrated sulfuric acid (2 levels) and nicks in the seed coat, on two collection years of G. flavum and G. acutidentatum. 2005 G. flavum had the greatest germination at 57 % with a 30- minute sulfuric acid scarification. 2003 G. flavum had 20% germination with the 60- minute acid scarification. G. acutidentatum seeds from 2003 and 2005 germinated with acid treatments but not as well as G. flavum. 2003 G. acutidentatum had 6% germination with 60-minute acid scarification and 2005 G. acutidentatum had 1.5% germination with 30-minute acid scarification. Stratification and scarification were evaluated together in the third trial. Additional seed lots; 2003 G. grandiflorum, 2003 G. corniculatum and 1999 G. corniculatum x flavum were included. Although each seed lot had varying responses to the treatments, 30-minute acid scarification combined with 30- or 45-day stratification at 8°C were the optimal pretreatments. The germination percentages for these treatments ranged from 60 to 92%. The final trial compared gibberellic acid to stratification to determine if GA could substitute for cold stratification. Hydrogen peroxide was also evaluated for comparison purposes. For all the seed lots, 30-minute acid scarification with 400 ppm or 500 ppm GA3 generated the greatest germination. The percentages for these treatments ranged from 58 to 95%. Gibberellic acid proved to be a substitute for cold stratification; however, seeds germinated slower than cold stratification. Germination with GA took approximately 10 days while stratified seed germinated in five days. G. grandiflorum and G. acutidentatum can be considered to have intermediate complex morphophysiological dormancy with a hard seed coat, while G. corniculatum appears to have only a hard seed coat.
Covers not scanned.
Keywords: Poppies -- Colorado; Seeds -- Dormancy -- Colorado